2021
DOI: 10.9734/arrb/2021/v36i530372
|View full text |Cite
|
Sign up to set email alerts
|

Clone x Tester Crosses on Compatibility Level of Sweetpotato (Ipomoea batatas L.)

Abstract: Evaluation of compatibility on sweetpotato is very important to determine the crossing parents to increase the compatibility of controlled cross-pollination.  This research was aimed to study the level of compatibility in controlled cross-pollination based on percentage of normal seedlings obtained from crosses. The research was conducted at Kendalpayak Experimental Station of ILETRI, Malang, Indonesia then followed by breaking seed dormancy and germination of seeds obtained. The genetic materials used were 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…A total of 1679 crosses produced 413 capsules (24.60%). Similar result was reported by Indriani et al (2021) who reported that 1747 crosses formed 432 fertile capsules (24.73%). The successful cross rate varied from 4.55% to 90.91% within family.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A total of 1679 crosses produced 413 capsules (24.60%). Similar result was reported by Indriani et al (2021) who reported that 1747 crosses formed 432 fertile capsules (24.73%). The successful cross rate varied from 4.55% to 90.91% within family.…”
Section: Discussionsupporting
confidence: 90%
“…The successful cross rate varied from 4.55% to 90.91% within family. However, it was reported that the success cross rate ranged from 50% to 100% (Baafi et al, 2016) and from 0.20% to 18.00% (Indriani et al, 2021). The success rates of crosses depend on various factors such as compatibility, the vigour of parents and weather conditions (Lebot, 2009).…”
Section: Genetic Compatibility and Successful Crosses' Ratementioning
confidence: 99%
“…Allogamy, present in the species, due to the mechanisms of self-incompatibility and sterility (Indriani et al, 2021), promotes a high degree of heterozygosity to the germplasm, reflecting in wide genetic variability for different phenotypic descriptors (Ritschel, 1998), both of the root (number, shape, weight, color of the epidermis and pulp) (Silva et al, 2012), and shoot (length of the stems, color, shape, and number of leaves) (Azevedo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%